A Comparative Clinical Study on Trushanadi Guggulu & Amrutadya Guggulu in the Management of Sthoulya with reference to Obesity - Pawan, Mane Akash (International Research Journal of Ayurveda & Yoga, 2022)
Introduction The disease Sthoulya is known to Indian Physicians since very olden time. All the Ayurvedic classics described the disease Sthoulya in detail. This disease has been listed under the eight most discarded personalities. The two terminologies have been widely used by Ayurvedic texts in reference to Obesity. i.e. Sthoulya and Medoroga. Materials and methods 40 patients irrespective of sex, socio-economic status, place, suffering from Sthoulya were selected for the study. Selected patients were randomly placed under two groups A and B with 20 patients in each group. Group‘A’: Patients under this group were treated by Trushanadi guggulu vati 500 mg 2 TID [General dose of Guggulu is 1-3 Maasha 14=1-3gm] with sukhoshna jal anupana for 30 days. Group‘B’: Patients under this group were treated by Amrutadya Guggulu vati 500 mg 2 TID [General dose of Guggulu is 1-3 Maasha 14 = 1-3gm] with sukhoshna jal anupana for 30 days. Result and Discussion-Both the treatment modalities have shown good result in the management of the disease Sthoulya. On Comparison between the Group-A (Trushanadi Guggulu) showed better results than Group B (Amrutadya Guggulu) in all the classical symptoms as well as on objective parameters.